-3f=8+f

Simple and best practice solution for -3f=8+f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3f=8+f equation:


Simplifying
-3f = 8 + f

Solving
-3f = 8 + f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1f' to each side of the equation.
-3f + -1f = 8 + f + -1f

Combine like terms: -3f + -1f = -4f
-4f = 8 + f + -1f

Combine like terms: f + -1f = 0
-4f = 8 + 0
-4f = 8

Divide each side by '-4'.
f = -2

Simplifying
f = -2

See similar equations:

| 2(6b-3)=-78 | | 3(x+7)=-6x-33 | | -19j-20=-6j-15j+18 | | 18=-2x-7x | | -20=31+3x | | 6b-12b+4c+6d= | | 2(x-5)3x=20 | | x+5x-7x+3-x=48 | | 1-(3y+3)=-8 | | -5q-10=-6q | | 4q-3y=27 | | 19-16-17h=-7-18h | | 1-3y+3=-8 | | -38(15x)+28(24x)=(75-75)+(-608+98) | | 5(3x-4)-3=5(x-2)+37 | | 8k=9+7k | | 10m+4=74mis | | -7-2x=2 | | -8d+6=20-10d+18 | | -9m=9-10m | | 24=8(x+2) | | -x+4+4=13 | | 2x(x-3)=18x^2-7x | | -608+98= | | -3(s+17)=-15 | | 9x-126=2x+49 | | -5(1+3x)=70 | | 19.9u+19.89=17.46-4.42+19.4u | | -38(-15x)+28(24x)= | | 6=-x-x | | 17j+-16j=19 | | 4x+264=8x |

Equations solver categories